Secondary Traumatic Stress and Burnout Among Muslim Nurses Caring for Chronically Ill Children in a Turkish Hospital. (March 2018) - Günüşen, Neslihan Partlak; Wilson, Marian; Aksoy, Burcu
Purpose: This study investigated secondary traumatic stress and its relationship to burnout among nurses working at a Turkish hospital.Design: A mixed-methods design included a cross-sectional survey administering the Professional Quality of Life instrument and Maslach Burnout Inventory to 106 nurses. Interviews with a subgroup of eight participants explored nurses' experiences and coping strategies related to caring for chronically ill pediatric patients.Results: High risk levels of secondary traumatic stress existed among 40.6% participants, and those over the age of 40 years were at greater risk. Two main interview themes emerged that identified (a) consequences and (b) coping strategies while caring for chronically ill children. Nurses experience emotional burdens and may purposefully distance themselves from chronically ill children. Social support from nurse colleagues and spiritual beliefs assist coping.Implications: Workplaces should acknowledge stressors inherent in chronic pediatric nursing care. Environments that welcome spiritual practices and actively encourage social support could address job hazards.